HAK KONSTITUSIONAL PERDA SYARIAT ISLAM - Thontowi, Jawahir (Al-Mawarid Jurnal Hukum Islam, 2006)
The pros and conts toward local acts based on Islamic Shariâah either from moslem or non moslem of Indonesian. According to the writer of this article that struggle of Indonesian moslem to implement Islamic Shariâah in Indonesia is inavoidable. In this connection, Indonesian gevernment and Indonesia people do not have rights to refuse it, even though the government have duty to protect toward the struggle to apply Islamic Shariâah. Because it becomes the fundamental rights and the freedom of Indonesian moslem to realize Islamic Shariâah, and that is protected by Indonesian constitution. Kata kunci: syariat Islam, perjuangan, konstitusi, dan hak.